2020
DOI: 10.1186/s12882-019-1671-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the measures of physical function, risk of falls and the quality of life in haemodialysis patients: a cross-sectional study

Abstract: Background: Impaired physical function due to muscle weakness and exercise intolerance reduces the ability to perform activities of daily living in patients with end-stage kidney disease, and by consequence, Health-Related Quality of Life (HRQoL). Furthermore, the risk of falls is an aggregate of physical function and, therefore, could be associated with HRQoL as well. The present study examined the associations between objective and subjective measures of physical function, risk of falls and HRQoL in haemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…The physical examinations included the following: (1) The Frailty and Injuries Cooperative Studies of Intervention Technique (FICSIT) was used to examine static balance (time) based on seven positional challenges; i.e. eyes open and closed with feet closely together, semi-tandem and full tandem stand and standing on the dominant leg with eyes open [25]; (2) The Tinetti test is considered the gold standard for examining gait dysfunctions based on 7 items: the initiation of gait, step length and height, step symmetry, step continuity, distinguished path, trunk and walking stance [26]. Patients scoring < 11 on 12 on the Tinetti test are considered to be at a higher risk of falls [27]; (3) For the five repetition Sit-to-Stand test (STS), patients were instructed to get from a seated to a standing position for 5 times as rapidly as possible with their arms folded across the chest [28].…”
Section: Physical Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical examinations included the following: (1) The Frailty and Injuries Cooperative Studies of Intervention Technique (FICSIT) was used to examine static balance (time) based on seven positional challenges; i.e. eyes open and closed with feet closely together, semi-tandem and full tandem stand and standing on the dominant leg with eyes open [25]; (2) The Tinetti test is considered the gold standard for examining gait dysfunctions based on 7 items: the initiation of gait, step length and height, step symmetry, step continuity, distinguished path, trunk and walking stance [26]. Patients scoring < 11 on 12 on the Tinetti test are considered to be at a higher risk of falls [27]; (3) For the five repetition Sit-to-Stand test (STS), patients were instructed to get from a seated to a standing position for 5 times as rapidly as possible with their arms folded across the chest [28].…”
Section: Physical Assessmentsmentioning
confidence: 99%
“…Physical impairments and haemodialysis (HD) therapy itself are major barriers for physical activity in patients with end-stage kidney disease (ESKD) [1,2]. Physical inactivity leads to a high risk for cardiovascular (CV) disease and results in a more extensive deterioration of physical performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…Backward stepwise regression was used to estimate the model that best predicts PF among AFO users. Hypothesized predictors of PF were selected a priori based on previous studies utilizing self-reported measures of PF [24][25][26][27][28][29][30][31]. The six factors were: gender, age, pain, fall history, AFO history, and ankle mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Em pacientes dialíticos, pode ser usado na promoção de saúde e controle de comorbidades, além de ajudar no controle de distúrbios motores e de equilíbrio. As intervenções para promover a qualidade de vida relacionada à saúde em pacientes com doença renal terminal devem focar na promoção da atividade física e no cuidado com a saúde mental do paciente, como descrito por López et al 8,10,15,19 .…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218unclassified